Novel Bispidine-Monoterpene Conjugates—Synthesis and Application as Ligands for the Catalytic Ethylation of Chalcones - Suslov, Evgeniy V.; Ponomarev, Konstantin Y.; Patrusheva, Oxana S.; Kuranov, Sergey O.; Okhina, Alina A.; Rogachev, Artem D.; Munkuev, Aldar A.; Ottenbacher, Roman V.; Dalinger, Alexander I.; Kalinin, Mikhail A.; Vatsadze, Sergey Z.; Volcho, Konstantin P.; et al. (Molecules (Basel, Switzerland), 2021)
A number of new chiral bispidines containing monoterpenoid fragments have been obtained. The bispidines were studied as ligands for Ni-catalyzed addition of diethylzinc to chalcones. The conditions for chromatographic analysis by HPLC-UV were developed, in which the peaks of the enantiomers of all synthesized chiral products were separated, which made it possible to determine the enantiomeric excess of the resulting mixture. It was demonstrated that bispidine-monoterpenoid conjugates can be used as the ligands for diethylzinc addition to chalcone C=C double bond but not as inducers of chirality. Besides products of ethylation, formation of products of formal hydrogenation of the chalcone C=C double bond was observed in all cases. Note, that this formation of hydrogenation products in significant amounts in the presence of such catalytic systems was found for the first time. A tentative scheme explaining the formation of all products was proposed.